2011
DOI: 10.1073/pnas.1109831108
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for complement in antibody responses is not explained by the classic pathway activator IgM

Abstract: Animals lacking complement factors C1q, C2, C3, or C4 have severely impaired Ab responses, suggesting a major role for the classic pathway. The classic pathway is primarily initiated by antigen–Ab complexes. Therefore, its role for primary Ab responses seems paradoxical because only low amounts of specific Abs are present in naive animals. A possible explanation could be that the classic pathway is initiated by IgM from naive mice, binding with sufficient avidity to the antigen. To test this hypothesis, a knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 65 publications
5
47
1
Order By: Relevance
“…Mice lacking complement-activating IgM, owing to a point mutation in the m H chain, showed a normal Ab response to sheep RBCs (48). Upon injection of specific IgM Abs, other mechanisms besides classical pathway activation might therefore also play a role for IgM-mediated Ag trafficking despite the requirement for C1q.…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking complement-activating IgM, owing to a point mutation in the m H chain, showed a normal Ab response to sheep RBCs (48). Upon injection of specific IgM Abs, other mechanisms besides classical pathway activation might therefore also play a role for IgM-mediated Ag trafficking despite the requirement for C1q.…”
Section: Discussionmentioning
confidence: 99%
“…SRBCs in sterile Alsever's solution were purchased from the National Veterinary Institute (HåtunaLab, Bro, Sweden) and stored at 4°C. SRBCs were washed in PBS three times before immunizing control mice with 5 Â 10 8 cells in 0.2 ml PBS in the tail vein 65 .…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies suggested that IgM-mediated enhancement of antibody production was dependent on activation of the classic complement pathway (5). However, a very recent report demonstrated that mice expressing IgM unable to activate complement (Cμ13 mice) had completely normal antibody production (9). Collectively, these observations suggest that much of the effector function of IgM, especially with regard to the enhancement of humoral immune responses and suppression of autoimmunity, is mediated through FcμR.…”
Section: (Unpaired T Test) (D)mentioning
confidence: 96%
“…It was proposed that IgM-antigen immune complexes enhanced B-cell survival by interacting with both B-cell receptor (BCR) and the complement receptor (CR) on B cells (2,8). However, very recently, knock-in mice expressing mutant IgM unable to activate complement were found to have completely normal antibody responses (9). Therefore, IgM-mediated enhancement of antibody production cannot be solely explained by activation of the classic complement pathway, and additional mechanisms are likely involved.…”
mentioning
confidence: 99%